2005
DOI: 10.2320/matertrans.46.148
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Unidirectionally Aligned SiC Whisker Reinforced Al Alloy Matrix Composite with Interfacial Thermal Resistance

Abstract: The effective thermal conductivities of unidirectionally aligned SiC whisker reinforced aluminum alloy matrix composites with different whisker diameters and volume fractions were measured from room temperature to 700 K. The thermal conductivity values parallel to the whiskers were found to be significantly higher than those in the normal direction. The thermal conductivities decrease as the whiskers' volume fraction is increased or their diameter is decreased. Effective-medium theory was used to calculate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Several studies [1][2][3][4][5] on the effective thermal conductivities of composites have shown that the interfacial thermal resistance is an important factor that must be considered when designing and developing composites with required thermophysical property, especially for composites containing nanoparticles or nanofibers. However the measurement of interfacial thermal resistance is still a difficult experimental problem.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [1][2][3][4][5] on the effective thermal conductivities of composites have shown that the interfacial thermal resistance is an important factor that must be considered when designing and developing composites with required thermophysical property, especially for composites containing nanoparticles or nanofibers. However the measurement of interfacial thermal resistance is still a difficult experimental problem.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal shrinkage behavior was analyzed at a heating rate of 10°C/min using a thermo‐mechanical analyzer (TMA: Mac Science TD5000S, Japan). Thermal diffusivity, α, was measured at room temperature up to 600°C by the laser flash method using a laser flash thermal diffusivity analyzer (LFA‐427, NETZSCH, Germany) . Only for the thermal diffusivity measurement, disk‐shaped samples with ~12.6 mm diameter and ~2 mm thickness were prepared by cutting tape laminates into disks and firing at 850°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental details were described in our previous report. 4) By analyzing the optical and SEM micrographs, we obtained the average lengths of the whiskers, the aspect ratio of the whisker clusters and the SiC volume fractions inside and outside the whisker clusters for each composite as listed in Table 1. The ratio of SiC volume fraction outside cluster to that inside cluster was defined as the parameter of reinforce-ment uniformity, when which equals to 1, it is uniform; and 0, the maximum nonuniform.…”
Section: Calculated and Measured Thermal Conductivity Of Sicw/al Compmentioning
confidence: 99%
“…(1) with p defined as the aspect ratio of the dispersion. The thermal conductivity of Al alloy matrix was measured 4) as 149 Wm À1 K À1 . The values of volume fraction and aspect ratio in Table 1 were used in calculation.…”
mentioning
confidence: 99%